Improve Assertiveness Towards Students Questions in The Language of Mathematical Logic - Firmansya, Arief; Hidayani, Sri Murni; Munawaroh, Nina Siti (International Journal of Technology and Modeling, 2022)
Assertiveness or Assertiveness in the perspective of Education is a domain of social skills among cooperation, responsibility, and self-control. Mathematics is a scary subject, this is one that relates to their assumptions. This fear causes math anxiety. When learning mathematics, it also includes math anxiety in the students' mathematical logic material. Mathematics anxiety in mathematical logic material is a form of students emotional response in mathematics subjects, listening to teachers when discussing mathematics lessons and solving student problems in mathematics, students' psychological conditions related to mathematics anxiety in students' mathematical logic materials and the effect of assertive attitudes towards mathematics anxiety in mathematics. students' mathematical logic material, which has an increase of about 2.65 from the average score obtained at Senior High Schools in Cirebon City